Patrón de presentación de apendicitis aguda en los últimos cinco años (20122016) en el Hospital Manuel Ygnacio Monteros Valdivieso IESS Loja - Agila Espinosa, Robinson José (2018)
Resumen:The objective of the study was to determine the pattern of presentation of appendicitis from 2012 to 2016 at the Manuel Ygnacio Monteros Valdivieso Hospital in Loja, in a population of 372 patients with a diagnosis of acute appendicitis. The predominant genus of appendicitis was male in 59.1% and between the ages of 31 and 40 years; 63.4% had a presentation <24 hours; 80.9% developed a typical presentation pattern. The Alvarado scale was used in only 2.4% of patients, and the most commonly used imaging test was ultrasound in 94.6% of patients. The most frequent preoperative diagnosis was acute appendicitis in 80.4% and the postoperative was uncomplicated appendicitis in 57.8%; 48.7% of the cases were in phase II (suppurative). There were no complications in 66.9%; and seroma was the predominant complication with 26.6% of all cases.